Design, Molecular Docking Studies and Toxicity Prediction of Some Novel 1, 2, 3-Triazole Derivatives Containing Piperazine Moiety as Antifungal Agents and CYP-51 Inhibitors - abozar roeintan; Fatemeh Fadaei Nobandegani (Fasa University of Medical Sciences, 2018)
Background & Objective: In this study, a number of new triazole derivatives, containing a 1, 2, 3-triazole ring attached to the piperazine moiety as antifungal agents and lanosterol 14 alpha-demethylase, (CYP51) inhibitors were docking studies conducted. In the following, the toxicity risks of the designed compounds, were predicted by existing software. Materials & methods: Initially, the chemical structures of all azole were designed using ChemBioDraw Ultra14.0 program, then transferred into Hyperchem software for energy minimization. After preparing, all of these chemical compounds were docked with the target enzyme in order to select the best inhibitor of the drug using the Auto Dock-Vina-1-1-2-win32.msi software. The results were analyzed using the Molegro Virtual Docking software. At the final stage, the toxicity risk prediction of compounds was performed by the OSIRIS program. Results: After checking the computation, 10 compounds of ligands that were the results of Docking, were selected according to the Gibbs free energy (least ΔG). Docking results revealed the azole-heme coordination, hydrogen bond, hydrophobic interactions were involved in the drug-receptor interactions. Among the all studied compounds, the best docking results were related to No. 5 displayed. In fact, this compound had the most negative ΔGbind (-10.85 Kcal/mol) that indicated favorable interactions with the key amino acid residues at active site of CYP51. Conclusion: In conclusion, according to the results of docking studies, biological evaluation and Toxicity Risk Prediction of designed Compounds, it can be concluded that Compound No. 5 can be considered as an effective antifungal agent and an inhibitor of the CYP51 enzyme